Factors influencing dietary behaviours in urban food environments in Africa: a systematic mapping review. Issue 14 (26th October 2020) - Osei-Kwasi, Hibbah; Mohindra, Aarti; Booth, Andrew; Laar, Amos; Wanjohi, Milka; Graham, Fiona; Pradeilles, Rebecca; Cohen, Emmanuel; Holdsworth, Michelle
Abstract: Objective: To identify factors influencing dietary behaviours in urban food environments in Africa and identify areas for future research. Design: We systematically reviewed published/grey literature (protocol CRD4201706893). Findings were compiled into a map using a socio-ecological model on four environmental levels: individual, social, physical and macro. Setting: Urban food environments in Africa. Participants: Studies involving adolescents and adults (11–70 years, male/female). Results: Thirty-nine studies were included (six adolescent, fifteen adolescent/adult combined and eighteen adult). Quantitative methods were most common (twenty-eight quantitative, nine qualitative and two mixed methods). Studies were from fifteen African countries. Seventy-seven factors influencing dietary behaviours were identified, with two-thirds at the individual level (45/77). Factors in the social (11/77), physical (12/77) and macro (9/77) environments were investigated less. Individual-level factors that specifically emerged for adolescents included self-esteem, body satisfaction, dieting, spoken language, school attendance, gender, body composition, pubertal development, BMI and fat mass. Studies involving adolescents investigated social environment-level factors more, for example, sharing food with friends. The physical food environment was more commonly explored in adults, for example, convenience/availability of food. Macro-level factors associated with dietary behaviours were food/drink advertising, religion and food prices. Factors associated with dietary behaviour were broadly similar for men and women. Conclusions: The dominance of studies exploring individual-level factors suggests a need for research to explore how social, physical and macro-level environments drive dietary behaviours of adolescents and adults in urban Africa. More studies are needed for adolescents and men, and studies widening the geographical scope to encompass all African countries.